LEGAL REGULATION OF THE RIGHT OF OWNERSHIP OF NATURAL RESOURCES IN THE ADOPTION OF AMENDMENTS TO THE CONSTITUTION OF THE REPUBLIC OF KAZAKHSTAN - Kurmanova, Айгуль Куанышевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article considers some issues of legal regulation of the ownership of natural resources. Analysis of the problems of the content of the real right to natural resources under consideration and related legal relations, as well as consideration of effective recommendations for its development and improvement based on the study of the fundamental principles is the purpose of writing the work. The relevance of the topic is justified by the social value of the realization of the right of ownership of natural resources for the population and the state in terms of meeting their needs. The use of general and special research methods in interaction is necessary to substantiate the author's opinion. The specificity of the object of research consists in the impossibility of isolating a separate natural resource from the environment, therefore it must be considered in interaction with it. The paper deals with the content of the concept of ownership of natural resources, which is complicated by the lack of a definition of the concept of "natural resources" in the legislation. The application of this institution in legislation and law enforcement practice along with the concept of "components of the natural environment" creates difficulties, especially in determining the priority in regulating the ownership of natural resources by civil or environmental (natural resource) legislation. This issue becomes relevant in the light of the adoption of amendments to the Constitution, in particular, regarding article 6. The constitutional provision on the ownership of natural resources by the people requires amendments to other normative legal acts regulating relevant issues in relation to this right. By the resolution of the Constitutional Council, this property is public law. In this regard, the question of applying the state property regime to this property may be controversial, since state and public property are different concepts in which state and public interests are the objects of the goals pursued.